Improving psychiatric nurses’ competencies in spiritual care and integration of clients’ religion/spirituality into mental healthcare: outcomes of an online spiritual care training program - Mahbobeh Shamsi; Zohreh Khoshnood; Jamileh Farokhzadian (BMC Psychiatry, 2022)
Abstract Background: Religion/spirituality (R/S), which is associated with individuals’ well-being and psychological health, plays a significant role in most clients’ lives in healthcare systems. Although clients in mental healthcare settings prefer their R/S to be employed in nursing care, R/S has neither been adequately integrated into mental healthcare nor discussed in the assessment and nursing interventions of mental healthcare. Evidence shows that most psychiatric nurses receive little or no training in spiritual care (SC) and are unable to integrate clients’ R/S into mental healthcare. To address this gap, the present study aimed to investigate the effects of an online SC training program on psychiatric nurses’ competencies in SC and the integration of clients’ R/S into mental healthcare. Methods: This experimental study was conducted with nurses working in a psychiatric hospital affiliated with a large University of Medical Sciences in southeast Iran. Random sampling was performed and 95 nurses were assigned to the intervention (n = 50) and control (n = 45) groups. Online SC training was conducted for the intervention group in four sessions over four weeks. Data were collected using the Self-Assessment of Spiritual Care Competency and R/S Integrated Practice Assessment Scale before and one month after the training program. Results: There were no significant differences between the two groups before training (p > 0.05). After the training, nurses in the intervention group obtained significantly higher scores in competencies in SC and integration of clients’ R/S into mental healthcare compared to the control group, with a considerable effect size (P < 0.05). Conclusion: The online training program positively affected psychiatric nurses’ competencies in SC and the integration of clients’ R/S into mental healthcare. Since SC is a critical need for clients, specifically in mental healthcare settings, nurses must receive continuous education to provide SC to various clients.